Analysis of risk and protective factors associated with retinal nerve fiber layer defect in a Chinese adult population - Wang, Ye-Nan; Wang, Ya-Xing; Zhou, Jin-Qiong; Wan, Qian-Qian; Fang, Li-Jian; Wang, Hai-Wei; Yang, Jing-Yan; Dong, Li; Wang, Jin-Yuan; Yang, Xuan; Yan, Yan-Ni; Wang, Qian; et al. (International journal of ophthalmology, 2023)
AIM: To investigate the risk and protective factors associated with the retinal nerve fiber layer defect (RNFLD) in a Chinese adult population. METHODS: This study was a cross-sectional population-based investigation including employees and retirees of a coal mining company in Kailuan City, Hebei Province. All the study participants underwent a comprehensive systemic and ophthalmic examination. RNFLD was diagnosed on fundus photographs. Binary logistic regression was used to investigate the risk and protective factors associated with the RNFLD. RESULTS: The community-based study included 14 440 participants. There were 10 473 participants in our study, including 7120 males (68.0%) and 3353 females (32.0%). The age range was 45-108y, averaging 59.56±8.66y. Totally 568 participants had RNFLD and the prevalence rate was 5.42%. A higher prevalence of RNFLD was associated with older age [P<0.001, odds ratio (OR): 1.032; 95% confidence interval (CI): 1.018-1.046], longer axial length (P=0.010, OR: 1.190; 95%CI: 1.042-1.359), hypertension (P=0.007, OR: 0.639; 95%CI: 0.460-0.887), and diabetes mellitus (P=0.019, OR: 0.684; 95%CI: 0.499-0.939). The protective factors of RNFLD were visual acuity (P=0.038, OR: 0.617; 95%CI: 0.391-0.975), and central anterior chamber depth (P=0.046, OR: 0.595; 95%CI: 0.358-0.990). CONCLUSION: In our cross-sectional community-based study, with an age range of 45-108y, RNFLD is associated with older age, longer axial length, hypertension, and diabetes mellitus. The protective factors of RNFLD are visual acuity and central anterior chamber depth. These can help to predict and evaluate RNFLD related diseases and identify high-risk populations early.
Gesehen am 04.01.2024